The Gould’s Toucanet Selenidera gouldii (Natterer, 1837) (Aves: Ramphastidae) as a monotypic species - Lima, Rafael Dantas (Zootaxa, 2024)
The Gould’s Toucanet Selenidera gouldii (Natterer, 1837) occurs mainly in eastern Amazonia, with a geographically isolated population in the northeast Brazilian state of Ceará. Based on two male specimens from the latter population that appeared to have a smaller body and bill with a relatively large black patch, Pinto & Camargo (1961) described the subspecies S. g. baturitensis. This taxon has long been known in museum collections only by the two male specimens mentioned in its description, but recently obtained specimens have now permitted a test of its validity with larger sample sizes. Here, I examined the largest sample of S. g. baturitensis studied to date to show that S. g. gouldii and S. g. baturitensis are just the east and west ends of a broad geographic pattern of smoothly clinal differences in morphometrics that were categorized as subspecies taxa.